2012
DOI: 10.4314/sajas.v42i5.3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors influencing milk urea nitrogen in South African Holstein cattle

Abstract: By knowing the milk urea nitrogen (MUN) content of dairy cows, the efficiency of dietary nitrogen utilization can be improved. The main objectives of this study were to identify and quantify environmental factors affecting MUN in South African Holstein cows. This will enable better interpretation of MUN results by accounting for such factors. A total of 82 900 test-day records of 9 901 Holstein cows from 40 herds participating in the South African National Milk Recording and Improvement Scheme (NMRIS) during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(22 reference statements)
1
4
0
1
Order By: Relevance
“…These results are comparable with 30.5 kg/day observed by Kgole et al (2012) in South African Holstein cattle and a 305 days average of 16.28 kg/day in Jersey cows by Meeske et al (2006). Mostert et al (2003) and Palladino et al (2010) reported a similar trend in production with higher milk yield in Holstein-Friesian cows than in Jersey cows.…”
Section: Resultssupporting
confidence: 83%
“…These results are comparable with 30.5 kg/day observed by Kgole et al (2012) in South African Holstein cattle and a 305 days average of 16.28 kg/day in Jersey cows by Meeske et al (2006). Mostert et al (2003) and Palladino et al (2010) reported a similar trend in production with higher milk yield in Holstein-Friesian cows than in Jersey cows.…”
Section: Resultssupporting
confidence: 83%
“…Physicochemical composition of cow milk is of great importance when it comes to nutritional value and its industrial processing ability, and varies according to several factors, among which are: breed, diet, udder health, lactation stage and physiological factors (pregnant or non-pregnant) (Aikman, Reynolds, & Beever, 2008;Dufour, Fréchette, Barkema, Mussell, & Scholl, 2011). Proteins, lipids and lactose are the constituents that vary the most during lactation (Kgole, Visser, & Banga, 2012;Sharma, Singh, & Bhadwal, 2011) generally showing higher values when lactation reaches advanced stages (Aganga, Amarteifio, & Nkile, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Season and milking systems influenced MU (P <0.001). Kgole et al (2012) noted that MUN was significantly affected by herd test day, year of calving, parity, number of milkings per day, and the lactation phase.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that, for accurate interpretation of the urea content, not only the feed factor but also other factors should be taken into consideration. These factors include breed (Rodriguez et al, 1997), parity (Broderick and Clayton, 1997;Godden et al, 2001;Sawa et al, 2011), body weight (Kohn et al, 2002), milk yield (Godden et al, 2001), fat and protein content, days in milk (DIM), milking frequency (Godden et al, 2001;Kgole et al, 2012), and month of the year (Arunvipas et al, 2003;Biswajit et al, 2011;Borkowska et al, 2012;Frand et al, 2003;Hojman et al, 2004;Kgole et al, 2012;Oudah, 2009;Rafieei, 2011;Rzewuska and Strabel, 2013b). In Polish breeding programmes, urea content in cow milk has been monitored since 2000.…”
Section: Introductionmentioning
confidence: 99%